2017
DOI: 10.1002/jcsm.12189
|View full text |Cite
|
Sign up to set email alerts
|

Changes in body composition and metabolic profile during interleukin 6 inhibition in rheumatoid arthritis

Abstract: BackgroundRheumatoid arthritis (RA) is a chronic inflammatory disease characterized by increased mortality associated with cardiometabolic disorders including dyslipidaemia, insulin resistance, and cachectic obesity. Tumour necrosis factor inhibitors and interleukin 6 receptor blocker licensed for the treatment of RA decrease inflammation and could thus improve cardiovascular risk, but their effects on body composition and metabolic profile need to be clarified. We investigated the effects of tocilizumab (TCZ)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
132
2
20

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(161 citation statements)
references
References 40 publications
7
132
2
20
Order By: Relevance
“…Elevated pro‐inflammatory cytokines, such as TNF‐α, IL‐1β, and IL‐6, can promote osteoclastic bone resorption and inhibit osteoblast differentiation, meanwhile suppress myogenic proliferation and differentiation as well as increase muscle degradation, resulting in joint destruction and muscle wasting. Although the effect of TNF‐α inhibitors on muscle mass is conflict in different studies, RA patients reported a significant gain in appendicular lean mass after 1 year treatment with IL‐6 receptor antagonist tocilizumab . Mechanical factors play significant roles in both muscle and bone through affecting on the differentiation of mesenchymal stem cells into osteoblasts and myotubes .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated pro‐inflammatory cytokines, such as TNF‐α, IL‐1β, and IL‐6, can promote osteoclastic bone resorption and inhibit osteoblast differentiation, meanwhile suppress myogenic proliferation and differentiation as well as increase muscle degradation, resulting in joint destruction and muscle wasting. Although the effect of TNF‐α inhibitors on muscle mass is conflict in different studies, RA patients reported a significant gain in appendicular lean mass after 1 year treatment with IL‐6 receptor antagonist tocilizumab . Mechanical factors play significant roles in both muscle and bone through affecting on the differentiation of mesenchymal stem cells into osteoblasts and myotubes .…”
Section: Discussionmentioning
confidence: 99%
“…Although the effect of TNF-α inhibitors on muscle mass is conflict in different studies, 12 RA patients reported a significant gain in appendicular lean mass after 1 year treatment with IL-6 receptor antagonist tocilizumab. 47 Mechanical factors play significant roles in both muscle and bone through affecting on the differentiation of mesenchymal stem cells into osteoblasts and myotubes. 48 Interestingly, recent studies indicated that both muscle and bone are considered as mutually impacted endocrine organs.…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia associates with various clinical complications in aging and cachexia‐associated chronic diseases; therefore, sensitive and reproducible measures of muscle mass are required to assess the evolution of muscle loss and to follow outcomes of therapeutic interventions directed at attenuation of tissue loss in order to improve outcome of patients. Considering availability of diagnostic CT scans in the majority of cachexia‐associated disease such as cancer and cirrhosis, as well as high accuracy and time efficacy of different software programmers for body composition measurements, finding an appropriate indicator of muscle mass, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…As we have now demonstrated that CER, a well‐known biomarker for muscle mass, is also associated with muscle performance, CER could potentially be utilized as a modifiable factor to improve post‐transplant patient and graft survival. Although, CER is a non‐invasive, easily accessible, inexpensive, and direct measurement of total body muscle mass; it is often not included in the imaging technique armamentarium available and applied for evaluation of muscle mass in clinical intervention studies and observational studies . Each of the imaging techniques that can be applied in clinical intervention and observational studies has its drawbacks, with expenses and availability as most important drawbacks for magnetic resonance imaging and computed tomography, while DEXA and muscle ultrasonography share the major disadvantage of not being able to measure intramuscular adipose tissue .…”
Section: Discussionmentioning
confidence: 99%